2016
DOI: 10.1515/jpm-2015-0414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quantitative fFn test in predicting the risk of preterm birth

Abstract: The QfFN thresholds of tests are a useful tool to distinguish pregnant women for PTB prediction risk <34 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…However, the specificity at 10 ng/ml was the lowest among the four thresholds, meaning that it may misclassify low‐risk women as high‐risk for sPTB, and increase additional risk from unnecessary interventions. In fact, a majority of quantitative fFN measurements fell below this threshold indicating an available application of 10 ng/ml threshold for a majority of patients who are theoretically at high‐risk of preterm birth 11,12 . Furthermore, meta‐regression and subgroup analysis confirmed significant usefulness of the 10 ng/ml threshold in predicting sPTB among asymptomatic women who are unlikely to deliver preterm.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the specificity at 10 ng/ml was the lowest among the four thresholds, meaning that it may misclassify low‐risk women as high‐risk for sPTB, and increase additional risk from unnecessary interventions. In fact, a majority of quantitative fFN measurements fell below this threshold indicating an available application of 10 ng/ml threshold for a majority of patients who are theoretically at high‐risk of preterm birth 11,12 . Furthermore, meta‐regression and subgroup analysis confirmed significant usefulness of the 10 ng/ml threshold in predicting sPTB among asymptomatic women who are unlikely to deliver preterm.…”
Section: Discussionmentioning
confidence: 86%
“…Table 1 presents the data from the included studies. Of the 15 studies, 13 described diagnostic performance of 10 ng/ml, 6,10–21 15 used 50 ng/ml, 6,10–23 12 used 200 ng/ml, 6,10–19,21 and 7 used 500 ng/ml 6,10,11,13,14,19,21 . Detailed information regarding study design, sample size, age of participants, and the thresholds used in each study is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There are publications comparing the predictive strength of qualitative and quantitative fFN measurements (16,17). A recent study showed that quantitative fFN test alone is equal effective to the combination of cervical length and qualitative fFN test (18).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the fetal fibronectin test was scored as positive or negative, with a cutoff of 50ng/ml [16, 18-28, 30, 31]. Subsequently, a quantitative test has been developed, and there is evidence that measuring the absolute concentration of fetal fibronectin is more informative than a categorical value of positive/ negative [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the issue of whether an increased concentration of fetal fibronectin in cervicovaginal fluid represents a marker of upper genital tract infection in patients with an episode of preterm labor remains unresolved. Some recent studies have evaluated the usefulness of quantitative fetal fibronectin testing to identify patients at risk for impending preterm delivery [32][33][34][35][36][37][108][109][110][111][112][113][114][115][116][117][118]. This study was conducted to determine if a quantitative cervical fetal fibronectin test can predict intraamniotic infection, intra-amniotic inflammation, histologic chorioamnionitis and a short amniocentesis-to-delivery interval in patients with preterm labor and intact membranes.…”
Section: Introductionmentioning
confidence: 99%